A Behavior Tree-Based Model for Supporting the Analysis of Knowledge Transferred in Software R&D Teams - Fernández Del Carpio, Alvaro (2016)
Software R&D teams require proper forms of representing knowledge at carrying out software engineering processes and researches. In this context, transfer of knowledge becomes a dynamic process because team members participating in the process acquire, communicate and integrate knowledge from different sources. In this paper, a behavior tree-based model is presented for representing knowledge generated from research and development activities. Through structured nodes representing pieces of knowledge, it is possible to identify key points of new challenges, concerns, issues, gaps, etc., and shed lights on new insights and knowledge of importance to team members, contributing to improve and provide solutions to the domain analyzed.